Recent Advances in Forward Brillouin Scattering: Sensor Applications - Sánchez, Luis A.; Díez, Antonio; Cruz, José Luis; Andrés, Miguel V. (Sensors (Basel, Switzerland), 2022)
In-fiber opto-mechanics based on forward Brillouin scattering has received increasing attention because it enables sensing the surrounding of the optical fiber. Optical fiber transverse acoustic resonances are sensitive to both the inner properties of the optical fiber and the external medium. A particularly efficient pump and probe technique—assisted by a fiber grating—can be exploited for the development of point sensors of only a few centimeters in length. When measuring the acoustic resonances, this technique provides the narrowest reported linewidths and a signal-to-noise ratio better than 40 dB. The longitudinal and transverse acoustic velocities—normalized with the fiber radius—can be determined with a relative error lower than 10−4, exploiting the derivation of accurate asymptotic expressions for the resonant frequencies. Using this technique, the Poisson’s ratio of an optical fiber and its temperature dependence have been measured, reducing the relative error by a factor of 100 with respect to previously reported values. Using a single-point sensor, discriminative measurements of strain and temperature can be performed, achieving detection limits of ±25 με and ±0.2 °C. These results show the potential of this approach for the development of point sensors, which can be easily wavelength-multiplexed.